Analysis of Teachers-Construct Reading Comprehension Revised Based on Taxonomy Bloom of English Textbook for Junior High School - Lulu Farhan (FKIP Universitas Cenderawasih, 2023)
The purpose of this study was to examine the six upper levels of the cognitive domain of Bloom's revised taxonomy used in the textbook titled Bahasa Inggris SMP/MTS Grade 7 Second Semester, namely memory level (C1), comprehension level (C2), Applied Level (C3), Analytical Level (C4), Assessment Level (C5) and Creative Level (C6). Using descriptive qualitative methods and content analysis, this study examined questions in reading comprehension tasks to determine the extent to which reading comprehension questions emphasized higher thinking skills (HOTS) and lower thinking skills (LOTS). The focus of this study is the analysis of the 7th second semester of the Bahasa Inggris SMP/MTS class. The researchers collected and listed questions on the reading comprehension task, then calculated the percentage and frequency of each cognitive level in each individual book chapter and in all four book chapters.Keywords:Â Teachers-Construct reading comprehension, Taxonomy Bloom Revised.